Memihak dan Memerdekakan Peserta Didik dalam Era Pendidikan Abad ke-21 melalui Project Perubahan - Ndraha, Epifani Diliati; Andriany, Liesna (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The Change in 21st Century Education Project proposes a transformation in learning approaches to support students and liberate them in the learning process. The data collection technique used in this research is library research. By integrating the principles of Ki Hadjar Dewantara's thinking with the demands of modern education, this project aims to ensure that every  individual has fair and relevant access to education. The results of this research show planned strategic steps through projects that can provide independent learning experiences, allow students to explore their ideas and personal strengths, and improve their ability to solve problems and think critically.